2020
DOI: 10.4152/pea.202001029
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor Based on Reduced Graphene Oxide Modified Carbon Paste Electrode for Curcumin Determination in Human Blood Serum

Abstract: A sensitive, accurate electrochemical sensor based on reduced graphene oxide modified carbon paste electrode (RGO/CPE) was developed to measure curcumin levels in human blood serum. The as-prepared electrode (RGO/CPE) was verified to outperform bare carbon paste electrode (CPE), with increased oxidation and reduction peaks at +0.505 V and +0.408 V, respectively. Curcumin measurement was performed using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. RGO/CPE showed a desirable linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…At present, various detection techniques have been successfully developed to determinate iodide ions and curcumin, such as chromatography [ 13 , 14 ], capillary electrophoresis [ 15 , 16 ], electrochemistry [ 17 , 18 ], and so on. Although these methods possess high accuracy and satisfactory sensitivity, they still display some disadvantages, such as sophisticated instrumentation, complicated sample pretreatment, tedious operation procedures, and unstable electrodes, which are limited to some extent to apply extensively.…”
Section: Introductionmentioning
confidence: 99%
“…At present, various detection techniques have been successfully developed to determinate iodide ions and curcumin, such as chromatography [ 13 , 14 ], capillary electrophoresis [ 15 , 16 ], electrochemistry [ 17 , 18 ], and so on. Although these methods possess high accuracy and satisfactory sensitivity, they still display some disadvantages, such as sophisticated instrumentation, complicated sample pretreatment, tedious operation procedures, and unstable electrodes, which are limited to some extent to apply extensively.…”
Section: Introductionmentioning
confidence: 99%
“…This was an irreversible oxidation process, in good accordance with previous reports. 53,54 A very small oxidation peak at the surface of GC/GO and GC/β-CD was also observed. These results demonstrated that CM intensely accumulated at the surface of GC/β-CD–rGO during the incubation, and, β-CD–rGO modified electrode significantly increased the sensitivity of electrode for CM sensing/measuring.…”
Section: Resultsmentioning
confidence: 93%
“…Nevertheless, there was a significant difference in curcumin oxidation peak current intensity between the c‐Zn and c‐Fe samples as higher and more intense peaks were observed for the former. The enhancement of curcumin oxidation peak current signified the higher concentration of curcumin in the media 54‐57 . Since a higher curcumin release has been observed for the c‐Zn, more oxidation of curcumin was expected to take place in the media compared to that of c‐Fe.…”
Section: Resultsmentioning
confidence: 99%